Efficacy and safety of transjugular intrahepatic portosystemic shunt in hepatic sinusoidal obstruction syndrome: systematic review and meta-analysis - Jiang, Xinghe; Ma, Xuan; Tian, Shuni; Peng, Lijun (Frontiers in Medicine, 2025)
Background:Hepatic sinusoidal obstruction syndrome (HSOS) is a rare but life-threatening liver condition. The clinical utility of transjugular intrahepatic portosystemic shunt (TIPS) for HSOS remains unclear.MethodsA systematic review and meta-analysis was performed across five databases (up to November 2024) to evaluate the efficacy and safety of TIPS in HSOS patients. Key outcomes included technical success, clinical response, portal pressure changes, survival, and complications.ResultsNineteen studies involving 465 patients were included. Pooled technical success and clinical response rates were 100 and 94.2%, respectively. TIPS significantly reduced portal pressure (mean PPG: −13.5 mmHg; PVP: −12.3 mmHg). The 3-month and 1-year survival rates were both 91.6%. Hepatic encephalopathy occurred in 13.2% of patients.ConclusionTIPS is a feasible and relatively safe treatment for HSOS, particularly in patients with pyrrolizidine alkaloid–induced HSOS (PA-HSOS). Further research is warranted to confirm its long-term benefits.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024620323, identifier CRD42024620323.